EFEK PEMBERIAN TEPUNG DAUN KELOR TERHADAP KONSUMSI DAN KECERNAAN PAKAN AYAM BROILER UMUR 5 MINGGU - asaf, Rahmawati; Sandiah, Natsir; Agustina, Dian (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2019)
This research was conducted to determine the effect of giving Moringa leaf flour to feed on consumptionand digestibility of broiler chickens aged 5 weeks. This research was conducted for two months, namelyin May and June in the Field Laboratory and Laboratory of Animal Husbandry, Faculty of AnimalHusbandry, Halu Oleo University, Kendari. The research material used was 12 broiler chickens aged 5weeks. Chickens are divided randomly into 12 cage units, without gender segregation (straigt run), each chicken is placed in individual cages. The design used was a completely randomized design with fourtreatment rations (R0 = concentrate; R1 = 98% R0 + 2% Moringa leaf flour; R2 = 96% R0 + 4% Moringaleaf flour and R3 = 94% R0 + 6% leaf flour Moringa, each treatment was repeated three times.The datawere analyzed using variance.The results showed that the administration of Moringa leaf flour in broilerfeed had no significant effect between treatments on consumption and digestibility so as not to increaseconsumption and digestibility of broiler chickens.Key words: Broiler, Moringa leaf flour, feed consumption, BO digestibility, BK digestibility